Intruder Detection and Prevention in a Smart Grid Communication System. (2015) - Vineeth V.V.,; Radhika, N.; Vanitha, V.
Abstract: Smart Grid is an electrical network that uses digital and other advanced technology to monitor and manage the transport of electricity from all generating sources to meet the varying demand of the end-users. The important nodes of the Smart Grid are the phasor measurement unit(PMU), Smart meter(SM) and phasor data concentrator(PDC). All PMU's within substation will form a communication network with a gate-way node called phasor data concentrator which updates data from PMU's within the cluster range. Proper management of data exchange between PMU's and PDC's are an essential thing to meet in the concept of Smart Grid. In this paper we are considering PMU as a sensor node and PDC as a central node and the data is exchanged between this nodes. Proposed intrusion detection algorithm, Packet loss avoidance using Time Division Multiple Access (TDMA) protocol and security algorithm improves system security in response to malicious attacks. Network simulator NS2 is used to create simulation scenario for detecting attacks. Hardware is tested using LPC2148 microcontrollers and Zigbee.